The effect of irregular breathing patterns on internal target volumes in four‐dimensional CT and cone‐beam CT images in the context of stereotactic lung radiotherapy. Issue 2 (11th January 2013) - Clements, N.; Kron, T.; Franich, R.; Dunn, L.; Roxby, P.; Aarons, Y.; Chesson, B.; Siva, S.; Duplan, D.; Ball, D.
Abstract : Purpose: : Stereotactic lung radiotherapy is complicated by tumor motion from patient respiration. Four‐dimensional CT (4DCT) imaging is a motion compensation method used in treatment planning to generate a maximum intensity projection (MIP) internal target volume (ITV). Image guided radiotherapy during treatment may involve acquiring a volumetric cone‐beam CT (CBCT) image and visually aligning the tumor to the planning 4DCT MIP ITV contour. Moving targets imaged with CBCT can appear blurred and currently there are no studies reporting on the effect that irregular breathing patterns have on CBCT volumes and their alignment to 4DCT MIP ITV contours. The objective of this work was therefore to image a phantom moving with irregular breathing patterns to determine whether any configurations resulted in errors in volume contouring or alignment. Methods: : A Perspex thorax phantom was used to simulate a patient. Three wooden "lung" inserts with embedded Perspex "lesions" were moved up to 4 cm with computer‐generated motion patterns, and up to 1 cm with patient‐specific breathing patterns. The phantom was imaged on 4DCT and CBCT with the same acquisition settings used for stereotactic lung patients in the clinic and the volumes on all phantom images were contoured. This project assessed the volumes for qualitative and quantitative changes including volume, length of the volume, and errors in alignment between CBCT volumes and 4DCT MIP ITV contours. Results: : When motion was introduced 4DCT and CBCT volumes were reduced by up to 20% and 30% and shortened by up to 7 and 11 mm, respectively, indicating that volume was being under‐represented at the extremes of motion. Banding artifacts were present in 4DCT MIP images, while CBCT volumes were largely reduced in contrast. When variable amplitudes from patient traces were used and CBCT ITVs were compared to 4DCT MIP ITVs there was a distinct trend in reduced ITV with increasing amplitude that was not seen when compared to true ITVs. Breathing patterns with a rest period following expiration resulted in well‐defined superior edges and were better aligned using an edge‐to‐edge alignment technique. In most cases, sinusoidal motion patterns resulted in the closest agreements to true values and the smallest misalignments. Conclusions: : Strategies are needed to compensate for volume losses at the extremes of motion for both 4DCT MIP and CBCT images for larger and varied amplitudes, and for patterns with rest periods following expiration. Lesions moving greater than 2 cm would warrant larger treatment margins added to the 4DCT MIP ITV to account for the volume being under‐represented at the extremes of motion. Lesions moving with a rest period following expiration would be better aligned using an edge‐to‐edge alignment technique. Sinusoidal patterns represented the ideal clinical scenario, reinforcing the importance of investigating clinically relevant motions and their effects on 4DCT MIP and CBCT volumes. Since most patients do not breathe sinusoidally this may lead to misinterpretation of previous studies using only sinusoidal motion.